Dynamics of femtosecond laser induced ablation from solid surfaces - Sokolowski-Tinten, K; Bialkowski, J; Cavalleri, A; Boing, M; Schuler, H; von der Linde, D (1998)
Femtosecond laser induced ablation from solid surfaces has been investigated by means of time resolved microscopy. On transparent materials ablation is initiated by dielectric breakdown and formation of a dense and hot surface plasma. Measurements of the plasma threshold yield values of a few times 10(13) W/cm(2) with little variation among different materials. This indicates that microscopic surface properties are responsible for surface breakdown. On absorbing semiconductors and metals near-threshold ablation is brought about by hydrodynamic expansion of the lasergenerated hot and pressurized matter. Upon expansion into vacuum initially metallic materials transform into a transparent state with a high refractive index. The observed behavior is related to general properties of matter in the liquid-gas coexistence regime.